Exploratory study of Jimmy Boyle's social connections, musical styles and his contribution to the music scenes of Malaysia - Lee, Sze May; Chan, Cheong Jan; Boyle, James P. S. (Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, 2014)
This paper is a qualitative study on a Malaysia 1960s’ legendary local composer, the late Jimmy Boyle. He is the composer for ‘Putera-puteri’, one of the most significant songs in Malaysia, which was performed in the 50th National Day Celebration and has been sung in school, choir competitions, and played by musicians all over the country until present day. Other than composing, he had also arranged, played and recorded for national and state functions, for schools and associations, for radio and television, and night clubs. Moreover, the popularity of his music is never limited in Malaysia. For instance, top jazz critics like Jerry Muchigan commented on his music, and some musicians and vocalists in America and Europe such as Jack Teagarden and Anneke Gronloh have played and recorded them. In 2014, a book denoted to the life and music of Jimmy Boyle was published by his own son, James Boyle. The purpose of this paper is to explore ways to deepen the understanding of Jimmy Boyle as a composer, in order to identify more information about his social connections, musical style and his contribution in music development of Malaysia beyond what is revealed in existing literatures and materials.